Liquid crystal polyimide aerogel with thermotropic liquid crystal behavior and preparation method thereof

By using condensation polymerization of diamine and liquid crystal dianhydride in polyimide aerogel and adding heat crosslinking agent, combined with directional refrigeration technology, polyimide aerogel with high thermal conductivity is prepared, which solves the problem of low thermal conductivity of polyimide aerogel, and achieves the application expansion in heat conduction and thermal management, while reducing production and processing costs.

CN119529370AActive Publication Date: 2025-02-28JIANGNAN UNIV

Patent Information

Application Number
CN202411645281.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-28
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The low thermal conductivity of existing polyimide aerogels limits its application in thermal conductivity, thermal management and thermal response, and when the thermal conductivity is improved by filling high thermal fillers, the mechanical properties of the material will deteriorate sharply, increasing challenges such as processing and production costs.

Method used

Polyimide aerogels with thermogenic liquid crystal behavior are prepared by condensation polymerization with diamine and liquid crystal dianhydride monomer and adding heat crosslinking agents, and their thermal conductivity is improved by directed freezing and heat crosslinking techniques.

Benefits of technology

On the basis of keeping the mechanical properties unaffected, high thermal conductivity is obtained, which is suitable for scenarios such as efficient thermal conductivity, rapid response to temperature changes, and high-temperature environment thermal management, reducing the production cost and processing difficulty of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529370A_ABST
    Figure CN119529370A_ABST
Patent Text Reader

Abstract

The invention discloses polyimide aerogel with thermotropic liquid crystal behavior and a preparation method thereof, and belongs to the field of polymer aerogel materials. The thermal conductivity of the polyimide aerogel with the thermotropic liquid crystal behavior at normal temperature is 0.07-0.08 W m <-1 > K <-1 >; the polyimide aerogel with the thermotropic liquid crystal behavior is obtained by directional freezing, thermal crosslinking and imidization of a polyamide acid aqueous solution. The polyimide aerogel with the thermotropic liquid crystal behavior has the advantages of being low in density, high in porosity, relatively high in heat conductivity, stable in structure and the like, the blank of application of liquid crystal polyimide materials in the aerogel field is filled, and the heat conduction performance of the polyimide aerogel is improved; and a foundation is provided for application of the polyimide aerogel material in the field of high-temperature intelligent deformation materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a liquid crystal polyimide aerogel with thermotropic liquid crystal behavior and a preparation method thereof, and belongs to the field of polymer aerogel materials. Background Art

[0002] Aerogel is a porous material formed by the aggregation of colloidal particles or polymer molecules. It has a continuous three-dimensional skeleton network, an open and interconnected porous structure, low density, high porosity and high specific surface area. It can be used in thermal insulation materials, sound insulation materials, energy storage devices, aerospace and other fields.

[0003] Polyimide is a kind of organic polymer with imide ring in the main chain. It has the advantages of high mechanical strength, good thermal stability and wear resistance. Whether it is used as a structural material or a functional material, its remarkable advantages have been fully recognized. In recent years, the research on polyimide aerogel has received much attention. It combines the excellent properties of polyimide and aerogel, so that it not only has the excellent properties of polyimide, but also has the outstanding characteristics of aerogel such as light weight, ultra-low density, high specific surface area, low thermal conductivity and low dielectric constant. However, it is precisely because of its low thermal conductivity that the application of polyimide aerogel may be subject to certain restrictions in certain specific cases. Fields requiring efficient heat conduction: In some industrial or scientific research environments, materials are required to have efficient thermal conductivity in order to quickly transfer heat. The low thermal conductivity of polyimide aerogel will become a disadvantage in these occasions because it will hinder the effective transfer of heat; in addition, such as thermal management in high temperature environments: although polyimide aerogel has a certain stability at high temperatures, its low thermal conductivity may make thermal management in high temperature environments more challenging. For example, polyimide aerogel is not the best choice in high-temperature equipment or systems that require rapid heat dissipation. Another example is the need for rapid response to temperature changes: In some applications, materials need to be able to respond quickly to temperature changes, such as temperature sensors or thermistors. The low thermal conductivity of polyimide aerogel may cause its response speed to slow down, thus limiting its application in these occasions.

[0004] At present, the strategy to improve the thermal conductivity of polyimide aerogel is mainly to add a certain amount of high thermal conductivity filler to the polyimide aerogel matrix to obtain a polyimide aerogel thermal conductive composite material. The advantage of this strategy is that the process is simple and convenient and easy to industrialize. The disadvantage is that in order to obtain a polyimide aerogel material with high thermal conductivity, a large amount of thermal conductive filler is often required, which easily leads to problems such as interface thermal barriers. At the same time, the addition of too much thermal conductive filler will inevitably cause the mechanical properties of the polyimide aerogel material to deteriorate sharply, which brings great challenges to material processing and production costs.

[0005] [Technical issues]

[0006] In the prior art, polyimide aerogel has low thermal conductivity, which seriously limits its application in thermal conduction, thermal management and thermal response. Although the thermal conductivity of polyimide aerogel can be improved to a certain extent by filling it with high thermal conductivity fillers, it inevitably causes the mechanical properties of polyimide aerogel materials to deteriorate sharply, bringing great challenges to material processing and production costs.

[0007] [Technical solution]

[0008] In view of the defects and shortcomings of the prior art, the present invention provides a polyimide aerogel with thermotropic liquid crystal behavior and a preparation method thereof. The polyimide aerogel with thermotropic liquid crystal behavior has high thermal conductivity while maintaining mechanical properties, and can be used in specific scenarios such as efficient heat conduction, rapid response to temperature changes, and thermal management in high-temperature environments.

[0009] Specifically, diamine and liquid crystal dianhydride monomers are subjected to condensation polymerization, and a thermal crosslinking agent is added to obtain a polyamic acid solution; the polyamic acid solution is slowly flowed into ultrapure water and stirred, and solvent exchange is performed, and polyamic acid dry fibers are obtained after freezing and drying. The polyamic acid dry fibers are then mixed with triethylamine in ultrapure water to obtain a polyamic acid aqueous solution, and the polyamic acid aqueous solution is injected into a special mold (with a copper plate at the bottom and polytetrafluoroethylene at the top), and after freeze drying, high-temperature thermal crosslinking and imidization, a liquid crystal polyimide aerogel with relatively high thermal conductivity is obtained.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] The first object of the present invention is to provide a liquid crystal polyimide aerogel with thermotropic liquid crystal behavior, wherein the thermal conductivity of the polyimide aerogel with thermotropic liquid crystal behavior at room temperature is 0.07 to 0.08 W m-1K -1 The polyimide aerogel with thermotropic liquid crystal behavior is obtained by directional freezing, thermal crosslinking and imidization of a polyamic acid aqueous solution.

[0012] The second object of the present invention is to provide a method for preparing the above-mentioned liquid crystal polyimide aerogel having thermotropic liquid crystal behavior, the preparation method comprising the following steps:

[0013] (1) subjecting a diamine monomer and a liquid crystal dianhydride monomer to a condensation polymerization reaction in N-methylpyrrolidone (NMP), and then adding a thermal crosslinking agent to continue the reaction to obtain a polyamic acid solution; placing the polyamic acid solution in ultrapure water for solvent exchange, and then freezing and freeze-drying to obtain polyamic acid dry fibers;

[0014] (2) adding the polyamic acid dry silk obtained in step (1) and triethylamine into ultrapure water and stirring them to obtain a polyamic acid aqueous solution;

[0015] (3) injecting the polyamic acid aqueous solution obtained in step (2) into an oriented mold, placing the mold in a freezer for oriented freeze molding, and freeze-drying it after molding to obtain a polyamic acid aerogel;

[0016] (4) The polyamic acid aerogel obtained in step (3) is subjected to thermal crosslinking and imidization to obtain a polyimide aerogel having thermotropic liquid crystal behavior, namely, a liquid crystal polyimide aerogel.

[0017] In one embodiment, the diamine monomer in step (1) includes one or both of 1,4-bis(4-aminophenoxy)benzene (TPE-Q) and 4,4'-diaminodiphenyl ether (ODA).

[0018] In one embodiment, the liquid crystal dianhydride monomer in step (1) is 4,4'-phenylenedioxydiphthalic anhydride (HQDPA).

[0019] In one embodiment, the thermal crosslinking agent in step (1) includes one or more of 4-ethynylaniline (4-EA), 4-phenylethynylphthalic anhydride (PEPA), and nadic anhydride (NA).

[0020] In one embodiment, the diamine monomer in step (1) is 1,4-bis(4-aminophenoxy)benzene and 4,4'-diaminodiphenyl ether, and the molar ratio of the two is 1:(0-1); the molar ratio of the diamine monomer to the liquid crystal dianhydride monomer is 1:(0.8-1.5), preferably 1:1.01-1.20.

[0021] In one embodiment, the molar ratio of the diamine monomer to the thermal crosslinking agent in step (1) is 1:(0-0.1), preferably 1:0.02.

[0022] In one embodiment, the polycondensation reaction in step (1) is carried out in an ice-water bath for 3 to 6 hours.

[0023] In one embodiment, the reaction time after adding the thermal crosslinking agent in step (1) is 3 to 6 hours.

[0024] In one embodiment, the solid content of the polyamic acid solution in step (1) is 8 to 15 wt %.

[0025] In one embodiment, the solvent replacement time in step (1) is 0.5 to 3 hours.

[0026] In one embodiment, the freezing and freeze-drying in step (1) is performed by freezing in a -60 to -80°C freezer for 2 to 5 hours, followed by drying in a -30 to -50°C freeze dryer for 60 to 72 hours.

[0027] In one embodiment, the concentration of polyamic acid in the polyamic acid aqueous solution in step (2) is 70-90 mg / ml.

[0028] In one embodiment, the stirring speed in step (2) is 500 to 1000 rpm, and the stirring time is 3 to 6 hours.

[0029] In one embodiment, the directional mold in step (3) is a cylindrical special mold with a copper plate at the bottom and polytetrafluoroethylene at the top.

[0030] In one embodiment, the freezing molding in step (3) is performed at a temperature of -80 to -20°C for a period of 1 to 24 hours.

[0031] In one embodiment, the freeze-drying temperature in step (3) is -50 to -20°C, and the time is 48 to 96 hours.

[0032] In one embodiment, the temperature of the thermal crosslinking in step (4) is 100 to 350° C., preferably 220 to 260° C., and the time is 1 to 3 hours.

[0033] In one embodiment, the imidization in step (4) can be carried out at the following temperature: 100-150° C. for 0.5-1.5 hours, 200-250° C. for 0.5-1.5 hours, and 300-350° C. for 0.5-1.5 hours.

[0034] In one embodiment, the thermal crosslinking and imidization in step (4) are performed under an inert atmosphere.

[0035] In one embodiment, the thermal crosslinking and imidization in step (4) is carried out in a tubular furnace under a nitrogen atmosphere.

[0036] The present invention also provides applications of the above-mentioned liquid crystal polyimide aerogel having thermotropic liquid crystal behavior in thermal management, thermal insulation materials, intelligent robots, aerospace vehicles, and intelligent wearable devices.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention prepares polyimide aerogel with thermotropic liquid crystal behavior for the first time. The preparation method is relatively simple and environmentally friendly, with low cost and good formability. The aerogel structure is relatively stable and can be designed into various shapes, which is suitable for use in a variety of application environments.

[0039] (2) The present invention uses a directional freezing strategy to generate a relatively ordered pore structure to prepare liquid crystal polyimide aerogel. It uses the microscopic order of liquid crystal molecules to moderately improve the intrinsic thermal conductivity of polyimide aerogel, which to a certain extent alleviates the contradiction of slow response rate caused by slow heat transfer in the polyimide aerogel skeleton, and provides ideas for preparing polyimide aerogels that can quickly respond to temperature changes. It lays a foundation for expanding the application of polyimide aerogels in specific scenarios such as those that require efficient heat conduction, rapid response to temperature changes, and thermal management in high-temperature environments;

[0040] (3) The thermal crosslinking agent added in the present invention causes the polyimide aerogel to crosslink and solidify during the high-temperature treatment process, which helps the liquid crystal aerogel to form a stable structure and provides a prerequisite for improving the formability of the polyimide aerogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a structural schematic diagram of a special orientation mold used in the present invention;

[0042] Figure 2 This is a microscopic structure diagram of the surface of the polyimide aerogel having thermotropic liquid crystal behavior prepared in Example 1 of the present invention;

[0043] Figure 3 DSC curves of the polyimide aerogel with thermotropic liquid crystal behavior prepared in Example 1 of the present invention and the polyimide aerogels of Comparative Examples 1 to 3 during heating;

[0044] Figure 4 This is a POM image of the polyimide aerogel having thermotropic liquid crystal behavior prepared in Example 1 of the present invention during the heating process;

[0045] Figure 5 This is a POM image of the polyimide aerogel prepared in Comparative Example 1 of the present invention during the heating process. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. The following specific implementation methods further describe the present invention.

[0047] Example 1

[0048] A method for preparing a liquid crystal polyimide aerogel having thermotropic liquid crystal behavior comprises the following steps:

[0049] (1) 1.0963 g of 1,4-bis(4-aminophenoxy)benzene and 0.2503 g of 4,4'-diaminodiphenyl ether were dissolved in 18.69 ml of N-methylpyrrolidone, 2.0317 g of 4,4'-diphenylenedioxydiphthalic anhydride were added, and the mixture was reacted in an ice-water bath for 3 h; 0.0118 g of 4-ethynylaniline and 5 ml of N-methylpyrrolidone were then added, and the reaction was continued for 3 h to obtain a polyamic acid solution having a solid content of 13.8%; the prepared polyamic acid solution was precipitated with ultrapure water, and then frozen in a -80°C freezer for 2 h, and then dried in a -50°C freezer for 72 h to obtain polyamic acid dry silk;

[0050] (2) 0.8 g of the polyamic acid dry silk obtained in step (1) was dissolved in 10 ml of ultrapure water, and 0.24 g of triethylamine was added thereto to accelerate the dissolution, and the mixture was stirred thoroughly to obtain a polyamic acid aqueous solution, wherein the concentration of the polyamic acid was 80 mg / ml;

[0051] (3) The polyamic acid aqueous solution obtained in step (2) is introduced into a special mold (the bottom is a copper plate and the top is polytetrafluoroethylene, Figure 1 As shown), the mold is then placed in a -40°C freezer for 6 hours, and after the freezing is completed, the mold is placed in a -50°C freeze dryer for freeze drying for 72 hours to obtain a polyamic acid aerogel;

[0052] (4) The polyamic acid aerogel obtained in the above step (3) is placed in a tubular furnace, and the polyamic acid is imidized and thermally cross-linked by high temperature in a nitrogen atmosphere. The high temperature treatment temperature program is 100°C for 1 h, 200°C for 1 h, 250°C for 0.5 h, and 280°C for 0.5 h, thereby obtaining a polyimide aerogel with thermotropic liquid crystal behavior, that is, liquid crystal polyimide aerogel, denoted as LCPIA.

[0053] Example 2

[0054] The only difference from Example 1 is that the concentration of polyamic acid in step (2) is adjusted to 60 mg / ml, the mass of polyamic acid dry silk is 0.6 g, and the amount of triethylamine added is 0.18 g; other conditions and parameters are the same as those in Example 1.

[0055] The properties of the obtained liquid crystal polyimide aerogel were measured, and it was found that the aerogel had defects such as surface cracks due to low solid content and poor morphology.

[0056] Example 3

[0057] The only difference from Example 1 is that the concentration of polyamic acid in step (2) is adjusted to 120 mg / ml, the mass of polyamic acid dry silk is 1.2 g, and the amount of triethylamine added is 0.36 g; other conditions and parameters are the same as those in Example 1.

[0058] The properties of the obtained liquid crystal polyimide aerogel were measured, and it was found that due to the high solid content, it was difficult to remove bubbles during the preparation process, resulting in defects such as foaming and irregular growth of the aerogel.

[0059] Comparative Example 1

[0060] The only difference from Example 1 is that the special mold in step (3) (the bottom is a copper plate and the top is polytetrafluoroethylene) is adjusted to a conventional silicone mold, and the other conditions and parameters are the same as those in Example 1. The obtained polyimide aerogel is recorded as PIA1.

[0061] Comparative Example 2

[0062] The only difference from Example 1 is that the diamine added in the adjustment step (1) is 1.0012 g of 4,4'-diaminodiphenyl ether (the amount of substance is the same as the total amount of diamine in Example 1), the dianhydride added is 1.4858 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (the amount of substance is the same as the amount of dianhydride in Example 1), and the other conditions and parameters are the same as those in Example 1. The obtained polyimide aerogel is recorded as PIA2.

[0063] Comparative Example 3

[0064] The only difference from Example 1 is that the diamine added in step (1) is adjusted to 1.0012 g of 4,4'-diaminodiphenyl ether (the amount of substance is the same as the total amount of diamine in Example 1), the dianhydride added is 1.4858 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (the amount of substance is the same as the amount of dianhydride in Example 1), and the special mold in step (3) (the bottom is a copper plate and the top is polytetrafluoroethylene) is adjusted to a conventional silicone mold. Other conditions and parameters are the same as in Example 1. The obtained polyimide aerogel is recorded as PIA3.

[0065] Performance measurement

[0066] 1. Liquid crystal polyimide aerogel structure characterization

[0067] Figure 2 This is a SEM electron microscope image of the surface of the liquid crystal polyimide aerogel prepared in Example 1. Figure 2 As shown, the interior of the liquid crystal polyimide aerogel is a porous structure, which is due to the pore structure left after the ice crystals sublimate during the freeze-drying process.

[0068] 2. Determination of thermal conductivity of liquid crystal polyimide aerogel

[0069] The thermal conductivity of the polyimide aerogel prepared in Example 1 and Comparative Examples 1, 2, and 3 was tested, and the thermal conductivity constant was measured by a thermal conductivity meter (TPS2500S): an aerogel sample with a length and width of about 3 cm and a thickness of about 1 cm was taken, and a 5501 type probe (probe diameter of 1 cm) was placed between the two samples, and the thermal conductivity was tested in the isotropic mode. At least 3 samples were tested in each group, and the thermal conductivity value was obtained by taking the average value, and the results are shown in Table 1:

[0070] Table 1 Thermal conductivity of polyimide aerogel at different temperatures

[0071] Temperature(℃) <![CDATA[Thermal conductivity (W m -1 K -1 )]]> Example 1 25 0.0706 Comparative Example 1 25 0.0529 Comparative Example 2 25 0.0631 Comparative Example 3 25 0.0613 Example 1 250 0.0920 Comparative Example 1 250 0.0814 Comparative Example 2 250 0.0775 Comparative Example 3 250 0.0770

[0072] Due to the low density and high porosity of aerogels, their thermal conductivity is generally low, usually between 0.01 and 0.05 W m -1 K -1 . As can be seen from Table 1, the liquid crystal polyimide aerogel prepared in Example 1 has a relatively high thermal conductivity. At the same time, it can be found that the closer to the liquid crystal generation temperature, the more obvious the improvement of its thermal conductivity. The reason is that the generated liquid crystal structure is microscopically ordered, which can reduce phonon scattering and form a heat conduction path. The liquid crystal polyimide aerogel is expected to expand the application of polyimide aerogel in specific scenarios such as those requiring efficient heat conduction, rapid response to temperature changes, and thermal management in high-temperature environments.

[0073] 3. Characterization of Liquid Crystalline Polyimide Aerogel Liquid Crystalline Structure

[0074] Figure 3 The DSC curves of the liquid crystal polyimide aerogel prepared in Example 1 and the polyimide aerogel prepared in Comparative Example 1 during heating are shown in FIG. Figure 3 It can be seen that during the heating process, the aerogel of Example 1 showed a complete endothermic peak (peak at 326°C), which is attributed to the gradual transformation of Example 1 from the amorphous phase to the liquid crystal phase; Figure 4 The POM image of Example 1 shows that no bright spots appear in the field of view during the heating process from 100°C to 300°C, but after 350°C, bright areas begin to appear in the field of view. This is because Example 1 has entered the liquid crystal generation temperature range.

[0075] And in Figure 3 It can be seen that the comparative example 1 only has a glass transition process (about 229°C), and no transition process from an amorphous phase to a liquid crystal phase occurs. This is attributed to the fact that the formation of liquid crystals requires a relatively ordered environment, and the comparative example 1 is not subjected to directional freezing, and no ordered structure is generated, which is not conducive to the formation of liquid crystals. At the same time, combined with Figure 5 The POM image of Comparative Example 1 during the heating process shows no bright spots in the temperature range of 100°C-350°C, proving that no liquid crystal phase is generated during the heating process of Comparative Example 1 without directional freezing.

[0076] And from Figure 3 It can be seen that both comparative examples 2 and 3 only have a glass transition process, and no amorphous phase to liquid crystal phase transition process. In summary, the preparation of this kind of polyimide aerogel with thermotropic liquid crystal behavior requires specific monomers to be directional frozen through a special mold (the bottom is a copper plate and the top is polytetrafluoroethylene) to form.

[0077] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A liquid crystal polyimide aerogel with thermotropic liquid crystal behavior, characterized in that: The thermal conductivity of the thermotropic liquid crystal polyimide aerogel at room temperature is 0.07-0.08 W m-1K -1 The polyimide aerogel with thermotropic liquid crystal behavior is obtained by directional freezing, thermal crosslinking and imidization of a polyamic acid aqueous solution.

2. A method for preparing the liquid crystal polyimide aerogel having thermotropic liquid crystal behavior according to claim 1, characterized in that: The preparation method comprises the following steps: (1) subjecting a diamine monomer and a liquid crystal dianhydride monomer to a condensation reaction in N-methylpyrrolidone, and then adding a thermal crosslinking agent to continue the reaction to obtain a polyamic acid solution; placing the polyamic acid solution in ultrapure water for solvent exchange, and then freezing and freeze-drying to obtain polyamic acid dry silk; the diamine monomer includes one or two of 1,4-bis(4-aminophenoxy)benzene and 4,4'-diaminodiphenyl ether; and the liquid crystal dianhydride monomer is 4,4'-diphenylene oxide diphthalic anhydride; (2) adding the polyamic acid dry silk obtained in step (1) and triethylamine into ultrapure water, stirring evenly to obtain a polyamic acid aqueous solution; (3) injecting the polyamic acid aqueous solution obtained in step (2) into an oriented mold, placing the mold in a freezer for oriented freeze molding, and freeze-drying it after molding to obtain a polyamic acid aerogel; (4) The polyamic acid aerogel obtained in step (3) is subjected to thermal crosslinking and imidization to obtain a polyimide aerogel having thermotropic liquid crystal behavior, namely, a liquid crystal polyimide aerogel.

3. The preparation method according to claim 2, characterized in that: The thermal crosslinking agent in step (1) includes one or more of 4-ethynylaniline, 4-phenylethynylphthalic anhydride, and nadic anhydride.

4. The preparation method according to claim 2, characterized in that: The diamine monomer in step (1) is 1,4-bis(4-aminophenoxy)benzene and 4,4'-diaminodiphenyl ether, and the molar ratio of the two is 1:(0-1); the molar ratio of the diamine monomer to the dianhydride monomer is 1:(0.8-1.5), preferably 1:1.01-1.

20.

5. The preparation method according to claim 2, characterized in that: The molar ratio of the diamine monomer to the thermal crosslinking agent in step (1) is 1:(0-0.1), preferably 1:0.

02.

6. The preparation method according to claim 2, characterized in that: The solid content of the polyamic acid solution in step (1) is 8 to 15 wt %.

7. The preparation method according to claim 2, characterized in that: The polyamic acid concentration in the polyamic acid aqueous solution in step (2) is 70-90 mg / ml.

8. The preparation method according to claim 2, characterized in that: The directional mold in step (3) is a cylindrical special mold with a copper plate at the bottom and polytetrafluoroethylene at the top.

9. The preparation method according to claim 2, characterized in that: The temperature of the thermal crosslinking in step (4) is 100 to 350° C., preferably 220 to 260° C., and the time is 1 to 3 hours.

10. Application of the liquid crystal polyimide aerogel with thermotropic liquid crystal behavior according to claim 1 or the liquid crystal polyimide aerogel with thermotropic liquid crystal behavior prepared by the preparation method according to any one of claims 2 to 9 in thermal management, thermal insulation materials, intelligent robots, aerospace vehicles, and intelligent wearable devices.

Citation Information

Patent Citations

  • Intrinsic high-thermal-conductivity liquid crystal polyimide film and preparation method thereof

    CN113105658A

  • Preparation method of fiber polyimide composite material with improved high-temperature mechanical and heat-conducting properties

    CN118684934A

  • Liquid crystal polyimide aerogel with excellent shape memory performance and preparation method thereof

    CN119529369A

  • Highly branched non-crosslinked aerogel, methods of making, and uses thereof

    US20170121483A1

Cited By

  • Liquid crystal polyimide aerogel with excellent shape memory performance and preparation method thereof

    CN119529369A

  • Liquid crystal polyimide aerogel with excellent shape memory performance and preparation method thereof

    CN119529369B